Radiolysis-induced Dosimetric Characterization of Aqueous Solutions of a Synthetic Dye for Gamma Dosimetry: Radiolysis of Aqueous Solutions of SO Dye - Hayat, Muhammad Khawar; Ramiza; Hussain, Taqmeem; Akhtar, Nasim; Khaliq, Rabia; Saeed, Abdul Hanan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this study, radiolysis-induced dosimetric response of the alkaline aqueous solutions of Sandalfix Orange C2RL (SO) dye was studied spectrophotometrically. Absorption peak (λmax) was determined by using a UV/VIS spectrophotometer. Absorbance (A) of the irradiated and un-irradiated sample solutions was measured at this λmax. Cs137 gamma radiation source was utilized for the irradiation of the sample solutions within 0.1-1 kGy and 10-100 kGy dose ranges, i.e., low and high dosimetry, respectively. The absorbance (A) of the sample solutions followed linearly and logarithmically decreasing functions with respect to absorbed dose (D) for low and high dosimetry, respectively. The % discoloration of the sample solutions was found to be increased exponentially with respect to absorbed dose (D) within low dosimetry; while logarithmic increase in %Ð was observed for high dosimetry.